Mualaf Mentoring Method in Bandung: a Case Study in Mualaf Care Indonesia Al-Muhtadin - Abdullah Muslich Rizal Maulana; Fadhilah Rachmawati; Dzihni Durratun Nikmah; Dhika Aziztya; Okta Taufika Rahma; Reizkiana Shiva (Religio Education, 2023)
This qualitative study aimed to discuss strategies to educate Mualaf -recent Muslim Mualafs- developed by Mualaf Care al-Muhtadin, Bandung. To arrive at a proper answer to that intended research question, this study utilized a descriptive-analytical method, elaborating the data derived from Mualaf Care al-Muhtadin Bandung that religious conversion is a change in one's religion from one religion to a new one, which changes one's beliefs entirely in the new Islamic faith. This study concluded that a Mualaf must receive complete guidance and encouragement to face challenges in many aspects, including social and economic disputes, invite to return to their previous faith affiliations, and lacking support from their family and colleagues. Consequently, following the experience of Mualaf Care al-Muhtadin Bandung, all Muslims must help Mualafs remain in Islam and encounter the challenges that come from their surroundings.